Estabilidade de cor e translucidez de materiais estéticos para CAD-CAM - Dalforno, Rafaelo Fagundes (2019)
Feldspathic ceramics and composite resin are among the most used aesthetic restorative materials in dentistry. A few years ago, the so-called Polymer Infiltrated Ceramic Network (PICN) was released on the dental market. According to its manufacturer, PICN featured ceramic and polymeric components. The objective of this study was to investigate the effect of dye immersion on color change and translucency of these three aesthetic restorative materials: PICN, feldsphatic ceramic (CF) and resin composite (RC). Twelve 1.2 mm-thick 10 mm-diameter disks of each material were produced, finished and immersed in red wine twice a day for 30 minutes each immersion. Color coordinates, L*, a* and b*, were measured before, 15 and 30 days after immersion, for calculation of color change (ΔE00, according to CIEDE 2000 formula) and translucency (contrast ratio), during the immersion time. Color change and translucency data presented a normal distribution and were submitted to one-way ANOVA and Tukey`s test. All tests were performed at a significance level of 5%. After 15 days of immersion, color change of RC was significantly greater than that of CF. PICN presented intermediate value, statistically similar to the other materials. After 30 days, color changes of the three materials were statistically similar. All color changes were perceptible and clinically unacceptable. None significant variation was observed in the contrast ratio of the three materials at 15 and 30 days. Findings indicate that PICN restorations would have levels of color change and translucency similar to those found in restorations of feldspathic ceramics and composite resin.